LITTORAL STATES’ DEFENSE DIPLOMACY IN MALACCA STRAIT THROUGH THE MALACCA STRAIT PATROL FRAMEWORK - Sulistyani, Yuli Ari (Jurnal Pertahanan dan Bela Negara, 2019)
Malacca Strait, as one of the strategic straits in world trade, often face various non-traditional security threats. In accordance with United Nations Convention on the Law of The Sea (UNCLOS), littoral states such as Indonesia, Singapore, and Malaysia are obligated to maintain the security in Malacca Straits, to ensure that world trades and world economic are not disrupted. This study analyzes how the Malacca straits patrol (MSP) framework is formed by littoral states in order to maintain the security stability in Malacca Strait. The authors employ qualitative method through literature study. The obtained data were analyzed using the theory of defense cooperation and concept of defense diplomacy. The results of the study conclude that MSP, which is consisted of the Malacca Straits Sea Patrol (MSSP), "Eyes-in-the-Sky" Combined Maritime Air Patrols (EiS), and the MSP Intelligence Exchange Group (IEG), is classified as a defense diplomacy activity in the form of multilateral contacts between military officials and multilateral military exercises aimed at increasing mutual trust and defense capabilities of each country. Keywords: Malacca Strait, Malacca Straits Patrol Framework, Threat, Defense Cooperation, Defense Diplomacy